The Influence of Oral Stimulation on the Improvement of Sucking Reflex and Weight Gain in Low Birth Weight Infants (LBW) at Bunda Patimah Primary Clinic - Hanum, Parida; Dela Pransiska, Putri; Yohana Eltania, Putri; Juni Ester Simamora, Putri; Br Purba, Sumaritoyani (Riviera Publishing, 2024)
LBW suffer from many problems, including hypothermia, respiratory distress syndrome, intracranial hemorrhage, hyperbilirubinemia, and hypoglycemia because the sucking reflex is weak, resulting in insufficient intake. This weakness in sucking is related to the maturity of the baby's nerve structure and the strength of the mouth muscles. Oral motor skills are one of the most important skills a baby has. The aim of this research is to determine the effect of giving oral stimulation on increasing the sucking reflex and increasing the weight of LBW babies. This research uses a type of quantitative research that uses a pre-test and post-test one group design (Notoatmodjo, 2018), with a Quasi-Experimental design without a control group that compares the evaluation results before and after treatment of respondents. Data were collected using Sucking Reflex and BB Increase observation sheets. The statistical test used is the Wilcoxon Signed Rank Test. The measurement results showed that after giving oral stimulation there was an increase in the sucking reflex and an increase in BW (P value = 0.000), namely an increase in the Sucking Reflex of the majority in the strong category as many as 30 people (93.7%), and those in the minority in the weak category as many as 2 people (6.3%). Meanwhile, in weight gain, the majority in the category increased by 28 people (87.5%), and the minority in the category did not increase by 4 people (12.5%). Based on the research that has been carried out, it was concluded that there is an effect of giving oral stimulation on the Sucking Reflex and Increase in Body Weight in LBW.